THE INFLUENTIAL FACTORS IN LANGUAGE CHOICE IN THE MULTILINGUAL SOCIETY IN SINJAI - herawati herawati (Pusbindiklat - LIPI, 2015)
This research aims to describe and explain the influential factors in language choice in the multilingual society while attempting to correlate such factors with domains and role relations. By using field research methods that is by participant’s observation and in-depth interview, the data were collected from daily speech events in the various domains. The languages used daily by the speech community in Sinjai are Konjo language, Buginese language, Malayic-Buginese language, and Indonesian language. In situations where the social context favors multiple interethnics contacts, however, some speakers may choose to incorporate features from a dominant variety into their speech. There are some influential factors in language choice in the inter-ethnic communication. Firstly, the language abilities of the speaker and the addressee which includes accommodation, mobility, and educational aspects. Second, the setting and the situation, both official and non-official. Third, the participants in the interaction, which includes social status, social distance, age, and presence of the third person.